2001
DOI: 10.1897/1551-5028(2001)020<1716:bolcan>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Lab-Contaminated and Native Polycyclic Aromatic Hydrocarbons to the Amphipod Corophium Volutator Relates to Chemical Desorption

Abstract: In the present study, the relationship between bioavailability of polycyclic aromatic hydrocarbons (PAHs) to benthic amphipods and the PAH desorption kinetics was examined. To that end, field-contaminated sediment was treated in three different ways. One subsample had no addition of PAHs and contained native PAHs only. To a second subsample, six PAHs (phenanthrene, fluoranthene, anthracene, pyrene, benzo[b]fluoranthene, and benzo[k]fluoranthene) were added in the laboratory. Two of the PAHs were added at highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(123 citation statements)
references
References 25 publications
(39 reference statements)
7
115
1
Order By: Relevance
“…PAH-BSAF values are not dependent on concentrations of PAHs in sediment (Kraaij et al 2001). Therefore it is unlikely that the lower BSAFs in experimental ponds were simply related to the higher PAH concentrations in sediments in those ponds.…”
Section: Biota-sediment Accumulation Factorsmentioning
confidence: 92%
See 1 more Smart Citation
“…PAH-BSAF values are not dependent on concentrations of PAHs in sediment (Kraaij et al 2001). Therefore it is unlikely that the lower BSAFs in experimental ponds were simply related to the higher PAH concentrations in sediments in those ponds.…”
Section: Biota-sediment Accumulation Factorsmentioning
confidence: 92%
“…Therefore it is unlikely that the lower BSAFs in experimental ponds were simply related to the higher PAH concentrations in sediments in those ponds. BSAFs are strongly influenced by sediment desorption kinetics (Lamoureux and Brownawell 1999;Kraaij et al 2001;Kukkonen et al 2004). In turn, sediment desorption kinetics are influenced by sediment characteristics.…”
Section: Biota-sediment Accumulation Factorsmentioning
confidence: 99%
“…Simple fugacity models based on K oc (Karikhoff, 1981), and K oc with a black carbon term (Accardi-Dey and Gschwend, 2003) failed to accurately or consistently predict the total levels of PAHs or PCBs that were readily desorbed. Use of a functionally defined readily desorbed HOCs fraction (Kraaij, 2001) is a rapid means of obtaining sediment-specific information on the bioavailability of HOCs. Additional work is required to relate readily desorbed HOCs to body burdens in benthic infauna.…”
Section: Hydrophobic Contaminant Partitioning Behaviourmentioning
confidence: 99%
“…The reasons for this included the more realistic and environmentally variable conditions in the field, coupled with the impacts of differing levels of biological organization and larger spatial scales. Similarly, Kraaij et al (2001) concluded that increased toxicity to PAHs in the laboratory compared to the field was related to increased bioavailability of PAHs in laboratory toxicity tests. However, Long et al (2001) in a review of amphipod sediment toxicity test results and corresponding benthic infauna diversity and abundance, concluded that "ecologically relevant losses in the abundance and diversity of the benthic infauna frequently corresponded with reduced amphipod survival in the laboratory tests."…”
Section: Field Versus Laboratory Responsesmentioning
confidence: 99%